الاطار العام والتصور المقترح لميثاق أخلاقي عربي للاختصاصيين الاجتماعيين - ميلود أ. مريم حسين (Aljameai)
Abstract: The ethical charter for social service has undergone several changes during its historical course, and its theoretical frameworks, and since this is not a shortcoming in itself, social specialists have the responsibility to work towards increasing attention to the ethical aspect during practice, while giving some attention to its theoretical aspect represented in the continuation of the registration process. "Codification", experimentation, and constructive criticism, so that the process of developing the ethical side, practically and theoretically, continues side by side in order to satisfy the cases and preserve their secrets. . Academic social work specialists should give some attention to ethical aspects during the educational process, both theoretical and practical, during field training, and perhaps they will realize that the social work profession still needs to develop the ethical aspect through the design of specialized training programs dealing with ethical aspects, in addition To organize scientific meetings and discussion seminars that include some professional practitioners, to clarify the ethical points contained in modern theoretical knowledge, to be formulated in the form of principles or instructions subject to analysis and experimentation, in order to continue the wheel of developing aspects of the profession, including the ethical aspect. . The practice centers and “practice institutions” have a major role in taking care of the ethical aspect of the profession, as the institutions follow up their professional staff to ensure their commitment and application of the ethics of the profession, as well as urging and encouraging them to pay attention to that aspect. The institutions of practice in social work must bear their responsibilities towards the rights of cases preserving their dignity, and preserving their privacy and secrets. The contemplator of the history of social service finds that it began from a moral perspective, and the same was the case during its evolutionary path, during more than a century of time, which confirms that it will not survive if it abandons its moral core on which it was based and for which is human service.